If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 7)(10x + 13) = y Reorder the terms: (7 + 2x)(10x + 13) = y Reorder the terms: (7 + 2x)(13 + 10x) = y Multiply (7 + 2x) * (13 + 10x) (7(13 + 10x) + 2x * (13 + 10x)) = y ((13 * 7 + 10x * 7) + 2x * (13 + 10x)) = y ((91 + 70x) + 2x * (13 + 10x)) = y (91 + 70x + (13 * 2x + 10x * 2x)) = y (91 + 70x + (26x + 20x2)) = y Combine like terms: 70x + 26x = 96x (91 + 96x + 20x2) = y Solving 91 + 96x + 20x2 = y Solving for variable 'x'. Combine like terms: y + -1y = 0 91 + 96x + 20x2 + -1y = 0 The solution to this equation could not be determined.
| 15=2m/3-1 | | 2x^2-4x-2x=0 | | -3-k/5=-10 | | g^2+32-40=0 | | 3xy+3yx=0 | | (2/3)^4/(3/4)^2 | | 39/8 | | 11x+15=5x+51 | | 69/20 | | Y^2-2y-27=-4y-3 | | x^3-6x^2-4x+8=0 | | 5s/6+7=-3 | | 7y+3y=180 | | 12-(x+3)=2x(-5+x) | | 7x+4=2x+16 | | 9k+4=49 | | U=7(3n+33)+8(n+1) | | -12=r/8-5 | | Y=.5x-8 | | e/4+8=1 | | -P-11-4= | | 3y+3(y-6)=8y-4(y+10) | | 16x+35=9x+21 | | b/6-16=-9 | | 3(2x+5)=13x+7-7x+8 | | 9x+34=5x+18 | | U=109+31(22) | | U=109+31(60) | | x^12-63x-64=0 | | 6x+34x-7=8(5x+6) | | 9n+6n= | | 12x^2+8x+6=0 |